2001
DOI: 10.1046/j.0953-816x.2001.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent tracer in pilocarpine‐treated rats shows widespread aberrant hippocampal neuronal connectivity

Abstract: Neuronal fibres of the hippocampal formation of normal and chronic epileptic rats were investigated by fluorescent tracing methods using the pilocarpine model of limbic epilepsy. Two months after onset of spontaneous limbic seizures, hippocampal slices were prepared and maintained in vitro for 10 h. Small crystals of fluorescent dye [fluorescein (fluoro-emerald) and tetramethylrhodamine (fluoro-ruby)] were applied to different hippocampal regions. The main findings were: (i) in control rats there was no suprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 50 publications
(58 reference statements)
3
45
0
Order By: Relevance
“…In accordance with the SE-induced change in PPF observed in wildtype mice, this finding suggests that in response to SE, specific regions in the wild-type brain react with adaptive responses that cannot be engaged in the RIM1␣ knock-out brain. Interestingly, both regions with reduced RIM1␣ mRNA levels, the DG and the CA1 region, exhibit aberrant neuronal connectivity in the chronic phase after pilocarpine treatment, in particular retrograde sprouting of the mossy fibers, CA1 neurons into area CA3, subicular neurons into area CA1, and increased connectivity between CA1 neurons and between the subicular and hilar cells (Lehmann et al, 2001). Surprisingly, chronic EEG recordings revealed that the acute pilocarpine-induced SE was largely not different when comparing RIM1␣ Ϫ/Ϫ and wild-type mice, even though there are manifold changes in the properties of different synapses.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the SE-induced change in PPF observed in wildtype mice, this finding suggests that in response to SE, specific regions in the wild-type brain react with adaptive responses that cannot be engaged in the RIM1␣ knock-out brain. Interestingly, both regions with reduced RIM1␣ mRNA levels, the DG and the CA1 region, exhibit aberrant neuronal connectivity in the chronic phase after pilocarpine treatment, in particular retrograde sprouting of the mossy fibers, CA1 neurons into area CA3, subicular neurons into area CA1, and increased connectivity between CA1 neurons and between the subicular and hilar cells (Lehmann et al, 2001). Surprisingly, chronic EEG recordings revealed that the acute pilocarpine-induced SE was largely not different when comparing RIM1␣ Ϫ/Ϫ and wild-type mice, even though there are manifold changes in the properties of different synapses.…”
Section: Discussionmentioning
confidence: 99%
“…The CA3 region of the hippocampus also exhibits cell dispersion, but we have not yet explored the functional consequences of that structural abnormality with respect to, for example, enhanced recurrent excitation (certainly a characteristic feature of CA3 circuitry) (Swann et al, 1990(Swann et al, , 1992. Although several different laboratories have demonstrated the development of abnormal synaptic reorganization, including recurrent excitation, in other areas of the hippocampus in human MTLE patients (Lehmann et al, 2000) and animal models of epilepsy (Perez et al, 1996;Lehmann et al, 2000Lehmann et al, , 2001Shao and Dudek, 2004), similar widespread abnormalities (e.g., in the CA1 subfield) have not yet been investigated in the p35Ϫ/Ϫ mouse.…”
Section: Structural and Functional Evidence Of Recurrent Excitationmentioning
confidence: 99%
“…Dextran-amine-coupled fluorescence and cresyl violet. To visualize dendritic and axonal processes of granule cells by anterograde and retrograde transport of dye, slices (two to four per specimen) were labeled with fluorescein or tetramethylrhodamine conjugated with dextran-amines (fluoro-emerald and fluoro-ruby; Molecular Probes, Leyden, The Netherlands), as described previously (Lehmann et al, 2001). In brief, small crystals of dye were inserted into a hilar lesion obtained after perpendicular penetration of the slice with a 27 gauge injection needle.…”
Section: Methodsmentioning
confidence: 99%